Developing Mobile Apps to Support Clinical Management of HIV Patients: An Observational Study - Roveta, Annalisa; Canonico, Massimo; Francese, Alessia; Sarchi, Eleonora; Ugo, Francesca; Massarino, Costanza; Penpa, Serena; Piceni, Giorgia; Barrera-León, Luisa; Apeddu, Alessandro; Picozzi, Emanuele; Chichino, Guido; Maconi, Antonio (Applied Clinical Informatics, 2025)
Human immunodeficiency virus (HIV) remains a significant global health challenge, especially in Europe, including Italy, where it affects thousands. Antiretroviral therapy (ART) has turned HIV into a manageable chronic condition, improving the quality of life and life expectancy for people living with HIV (PLWH). Enhancing health-related quality of life (HRQoL) is essential, as it positively influences therapy adherence.The objective of the study was to evaluate the impact of the AURORA system, a self-monitoring tool designed for HIV+ patients, on their quality of life and healthcare management. We aimed to assess specific aspects of well-being, including sleep quality, depression, and anxiety disorders, while also measuring patient satisfaction with the application and adherence to ART.Fifty HIV+ patients on a stable antiretroviral regimen for at least 6 months were recruited from the Infectious Diseases Department of AOU-AL and asked to download a health monitoring app. ART adherence, HRQoL, and project satisfaction were assessed through patient self-reports.A total of 50 virologically suppressed HIV+ patients were enrolled in the study, of whom eight were non-compliant with the protocol. The AURORA app was used from June 2023 to March 2024, demonstrating optimal adherence to therapy among compliant patients. A significant proportion (26.2%) reported that they found the app very beneficial, while less than 5% reported no benefit at all. Common feedback included the inability to modify certain notification settings. The results indicated significant correlations between sleep disturbances, anxiety, and depression. Patients liked the daily assessment of self-care, synchronously monitored by clinicians, and guaranteed privacy, but several improvements need to be made.Participant feedback will guide app enhancements, such as phone call integration, health data monitoring, and e-learning features to improve patient-clinician communication and personalized education. Future directions may include extending the project and adding a control group not using the app, allowing a comparison of therapy adherence and patient satisfaction between users and non-users. This would provide concrete data on the app's effectiveness in promoting therapy compliance.
Keywords: HIV/AIDS; mobile applications; digital health